Spiritual leadership among nursing educators: a correlational cross-sectional study with psychological capital - Mennat-Allah G. Abou Zeid; Ayman Mohamed El-Ashry; Manar Ahmed Kamal; Mahmoud Abdelwahab Khedr (BMC, 2022)
Abstract Background Spiritual leadership is the most positive leadership style accepted by positive organizational behavior scholars that contributes to psychological capital. Spiritual leadership could be a critical organizational resource for followers. The study aims to examine the levels of spiritual leadership and psychological capital among nursing educators and determine the relationship between spiritual leadership and psychological capital among nurse educators. Methods A cross-sectional design was applied using two tools: spiritual leadership and psychological capital scales. Over 3 months, data were collected from 213 nursing educators. Results The spiritual leadership level is moderate to high (49.8 and 38.5%). The psychological capital level is high (63.4%). The association between spiritual leadership and psychological capital is a strong, positive, and highly significant correlation (R-value = 0.63, P = 0.001). The regression analysis predicted that male participants were expected to have more spiritual leadership and psychological capital than females. Conclusion It can be concluded and validated how important it is to develop and practice spiritual leadership to foster followers' psychological capital. Implications of nursing management as nursing leaders must have spiritual competencies to promote workplace spirituality on the daily agenda as a foundational area in management.